“Four-sight”: an application of futures techniques to develop emerging economy responses to the Fourth Industrial Revolution - Bosch, Rafeeq Allie (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.